2022
DOI: 10.1101/2022.08.02.502523
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mouse B2 SINE elements function as IFN-inducible enhancers

Abstract: Regulatory networks underlying innate immunity continually face selective pressures to adapt to new and evolving pathogens. Transposable elements (TEs) can affect immune gene expression as a source of inducible regulatory elements, but the significance of these elements in facilitating evolutionary diversification of innate immunity remains largely unexplored. Here, we investigated the mouse epigenomic response to type II interferon (IFN) signaling and discovered that elements from a subfamily of B2 SINE (B2_M… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 86 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…Since the higher IFN-β response detected upon proton irradiation was associated with an increased expression of several TEs (Figure 4F, 4G), we explored individual TEs at the single cell level. We identified a stronger upregulation of several TEs in the clusters of proton-irradiated cells (Figures S9A and S9B), including the B2_Mm2 TE, which was shown to be a potent IFN-β enhancer 40 . Interestingly, cells expressing a high TE score and ISGs exhibited lower expression of the H3f3a and H3f3b genes (Figures 5K and S9C), which are key heterochromatin regulators involved in TE silencing 30 .…”
Section: The Identified Population Of Sox9+ Cells (Figures 5c 5e Left...mentioning
confidence: 94%
“…Since the higher IFN-β response detected upon proton irradiation was associated with an increased expression of several TEs (Figure 4F, 4G), we explored individual TEs at the single cell level. We identified a stronger upregulation of several TEs in the clusters of proton-irradiated cells (Figures S9A and S9B), including the B2_Mm2 TE, which was shown to be a potent IFN-β enhancer 40 . Interestingly, cells expressing a high TE score and ISGs exhibited lower expression of the H3f3a and H3f3b genes (Figures 5K and S9C), which are key heterochromatin regulators involved in TE silencing 30 .…”
Section: The Identified Population Of Sox9+ Cells (Figures 5c 5e Left...mentioning
confidence: 94%
“…B2 DNA carries a TATA box; therefore, it binds to TBP and Pol II to drive Pol II transcription in an orientation opposite to that of Pol III transcription (Ferrigno et al, 2001;Lunyak et al, 2007), which is also suggested to be involved in the formation of chromatin boundaries. It was recently shown that many copies of B2_Mm2 bind to STAT1 and likely generate mouse-specific interferon-inducible genes upon viral and microbial infection (Horton et al, 2023).…”
Section: Sine Classmentioning
confidence: 99%
“…For example, it has been reported that L1 copies are involved in X-chromosome inactivation in mice (Chow et al, 2010). On the other hand, SINEs are enriched in the gene-rich A compartments, and some of their copies regulate gene expression by serving as binding sites for transcription factors (Román et al, 2008;Roman et al, 2011;Schmidt et al, 2012;Tan et al, 2013;Thybert et al, 2018;Kaaij et al, 2019;Ichiyanagi et al, 2021;Gassler et al, 2022;Gualdrini et al, 2022;Horton et al, 2023;Kaemena et al, 2023;Osipovich et al, 2023). Some LTR retrotransposons, especially those of ERVK, are enriched in the B compartments, whereas those of ERVL are often found in the A compartments.…”
Section: The Distribution Of Retrotransposons May Be Linked To Their ...mentioning
confidence: 99%